Cosmophanie, paysage et haïku - Augustin Berque (Projets de Paysage)
As shown by, among others, the “first landscape” (hatsugeshiki) kigo (season word), the landscape occupies a prominent place among haiku themes. Several examples are analysed in this article, not from a literary angle but in an attempt to define how the haiku and the landscape are a part of a cosmophany (world-appearance of a certain environment). As in any cosmophany, this one expresses an ordered arrangement (a kosmos) of fundamental values from a certain culture, connecting this to a given natural environment to transform it into the specific milieu of that culture, and therefore the one which suits it best.